Data Performativity and Health: The Politics of Health Data Practices in Europe. (March 2020) - Blouin, Gabriel G.
The European Commission produces the European Core Health Indicators (ECHI), a database containing different tools used to compare European Union (EU) countries and recommend policy changes. The ECHI feeds multiple reports and documents and finds its way into health policies. From this arises the main research question addressed in this paper: How is health in Europe influenced by ECHI data practices? Specifically, we look at how some health issues or populations are prioritized or dismissed, which ultimately shapes the meaning of and knowledge about health in Europe. To do so, we first develop the conceptual framework of "data performativity, " underlining how data practices shape their object/subject. We then explore the politics of evidence behind the ECHI health data that materialize into (1) the absence of some health issues and populations and (2) the hypervisibility of neoliberal health. In the end, we argue, the ECHI serves as a site of individual, collective, and political identity enunciation.